Who gets what, where: To what extent are inequalities in distribution of Norwegian child welfare service measures related to spatial and temporal variation - Norunn Hornset (PLoS ONE, 2025)
Inequality has long been a persistent issue, but it has intensified since the turn of the millennium and is now considered one of the most urgent challenges of our time. Even in Norway, which is traditionally considered an egalitarian society, there is an increase in income inequalities. Inequality disproportionately affects marginalized groups; one especially marginalized group is young people with experience in child welfare services. Traditionally, inequality in child welfare services has been explored from individual or family perspectives. However, it has been argued that spatial and temporal dimensions also influence the distribution of these services. This paper looks beyond individual and family factors by examining how temporal and spatial factors affect distribution of child welfare services in Norway. Using registry data for individuals born in Norway in 1995 and 2005, the study combines logistic regression analysis with hotspot analysis (Getis-Ord Gi*) in GIS. The findings reveal that both spatial and temporal factors significantly influence the distribution of child welfare services in Norway. In particular, living in rural municipalities is associated with reduced access to services. As a result, the national principle of equal access to services across all regions is not being upheld.